Code-Switching Occurring in the Business Transaction at Pasar Atom - Yohanna (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study drew upon the theoretical frameworks as proposed by Hoffmann (2014) to examine the types of code-switching employed by the shopkeeper with her eight respective customers in their business transactions. This study was carried out using a qualitative approach focusing on the shopkeeper’s and her eight respective customer’s sentences containing code-switching. The findings revealed that the shopkeeper engaged in all the three types of code-switching, whereas among the eight customers there were six customers who used two types and the other two customers who used all three types of code-switching. The code-switching between the shopkeeper and her respective eight customers used codes in Indonesian and Javanese. The study concluded that the application of code-switching by the shopkeeper and her eight respective customers might be influenced by her relationship with her eight respective customers.